Harry Potter and the order of the Pheonix - Yates, David, 1963-; Radcliffe, Daniel, 1989-; Grint, Rupert, 1988-; Watson, Emma, 1990-; Staunton, Imelda, 1953-; Goldenberg, Michael; Barron, David; Heyman, David; Warner Bros Pictures; Heyday Films production (California : Warner Bros, 2007)
As Harry enters his fifth year at Hogwarts Academy, rumors of Lord Voldemort's return divide the wizarding world, and despite the insistence that there is no danger Harry and his friends start a group called Dumbledore's Army to prepare for a battle with Lord Voldemort and his followers
Title from title screen
Based on the novel by J.K. Rowling
Casts : Daniel Radcliffe, Rupert Grint, Emma Watson, Robbie Coltrane, Ralph Fiennes, Michael Gambon, Brendan Gleeson, Jason Isaacs, Gary Oldman, Imelda Staunton, Alan Rickman, Maggie Smith
In Chinese and Malay subtitles
Keywords: Wizards -- Drama; Magic -- Drama; Hogwarts School of Witchcraft and Wizardry (Imaginary place) -- Drama